Nutritive value and fermentative characteristics of pinneaple waste and poultry litter silages - Gutiérrez, Francisco (2003)
By using laboratory silos, mixtures of pinneaple waste and poultry litter were ensiled during 60 days to study fermentation and quality characteristics. Ratios of pinneaple and poultry litter used were based on 100% pinneaple; 90:10; 80:20 and 70:30 wet basis, respectively. Materials were arranged on layers in such a way that the upper and lower were pinneaple waste. The addition of poultry litter in the mixture increased dry matter, crude protein, ADF, lignin, silica and mineral content of the silages, but decreased ether extract, NDF, hemicellulose, cellulose and IVDMD. Addition of poultry litter increased silage pH, ammonia nitrogen, butiric acid content and decreased lactic acid, acetic acid and ethanol concentrations. It is concluded that a mixture of 90:10 of pinneaple waste and poultry litter resulted on good fermentation silages with pH values of 3.62, 16% amonia-nitrogen; lactic acid 3.19 % DM, and, butiric acid 0.06% DM. The nutrient content of this silage was 13% DM, 10% CP, 2% EE, 65% FND, 15% NSC, 35% FAD, 30% hemicellulose, 30% cellulose, 3.9 lignin, 0.43% silica, 1.28% Ca, 0.73% P, 0.20% Mg and 79% IVDM digestibility.